Generic Teaching Skills in ELT - Pangaribuan , Tagor (Pascasarjana Universitas HKBP Nommensen, 2021)
This paper is a based on a grounded research problem on the relationship between the world of professional work and education. Within the umbrella of Indonesian Quality Framework (KKNI), the focal research question is: How can we equip English Teacher with accountable Generic Competence in NNs setting Indonesia? This research addresses a tour-of-duty primitive question in Teaching English as a Foreign Language in NNs setting Indonesia in general, and particularly at English Department in various Institute of Education in Indonesia. This research report is within the framework of grounded research on Designing English Learning and TEFL Text Standard following Indonesian Quality Framework perspective (KKNI, hibah kompetisi, 2016), sponsored by Indonesian Directorate of Higher Education.